An Overview of Institutional Research - Stenquist, Lee B.; Utah State Univ., Logan ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The role of institutional research is expanding and gaining in importance. Institutional research must fully examine and criticize the institution, including its purpose and values. Institutional research officers must concern themselves with academic and administrative functions and processes and participate actively in the planning and decisionmaking processes. The information provided by the institutional research officers must be selective, meaningful, bring about changes for improvement, and allow experimentation in solving existing and future problems of higher education, particularly the institution's role. (Author)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Colleges; Educational Improvement; Educational Objectives; Educational Researchers; Educational Responsibility; Higher Education; Institutional Personnel; Institutional Research; Institutional Role; Universities